Analysis of primary care prescription trends in England during the COVID-19 pandemic compared against a predictive model. Issue 3 (3rd August 2021) - Frazer, John Scott; Frazer, Glenn Ross
Abstract : Objectives: The COVID-19 pandemic has had an unprecedented impact across primary care. Primary care services have seen an upheaval, and more and more patients are engaging in telephone consultations in order to maintain social distancing. In the present study, we seek to quantify the effect of the pandemic on primary care prescribing. Design: We conducted a retrospective analysis of the English Prescribing Dataset from January 2014 to November 2020, totalling 7 542 293 921 prescriptions. Data were separated into prepandemic and pandemic sets. A Holt-Winters predictive model was used to forecast individual drug prescribing based on historic trends. Observed data were compared with the forecast quantitatively and qualitatively. Setting: All prescriptions signed in England and dispensed during the years 2014–2020. Participants: All residents of England who received a prescription from primary care facilities during 2014–2020. Results: Prescribing of numerous health-critical medications was above predicted in March 2020, including salbutamol (53.0% (99% CI (41.2% to 66.9%))), insulin aspart (26.9% (99% CI (18.5% to 36.6%))) and tacrolimus (18.6% (99% CI (8.3% to 31.1%))). Medications for end-of-life symptom control increased in April, including levomepromazine hydrochloride (94.7% (99% CI (54.6% to 163.0%))). Medications requiring face-to-face visits decreased, including the local anaesthetic bupivacaine hydrochloride (86.6% (99% CI (89.3% to 82.0%))). There was no observed change in medications relating to type 2 diabetes, hypertension or mental health conditions. Conclusions: Significantly increased prescribing of several medications was observed, especially among those critical for health. A dramatic spike in end-of-life prescribing highlights the adversity faced by community practitioners during 2020. Medications involving face-to-face consultations declined, as did contraceptives, travel-related vaccines and drugs used in dementia and Parkinson's disease. Drugs relating to type 2 diabetes, hypertension and mental health were unchanged.